PEMBAHARUAN SISTIM PERPAJAKAN DAERAH DI INDONESIA INDONESIAN LOCAL TAXATION REFORM - Sitepu, Budi (Jurnal Legislasi Indonesia, 2011)
Indonesia has experienced a number of phases on its local taxation systems, thelatest one was indicated by promulgation of Law No. 28 Year 2009 concerning localtaxes and local charges. A significant changes has been made by the said law, suchas limitation of local taxes, local taxing empowerment, improvement of control system,and optimalization of tax collection and the use of local tax revenues. Limitation oflocal taxes is done by determining 16 type of local taxes (5 type provincial taxes and11 type region/city taxes) and implementing a ‘closed-list’ systems. Local taxingempowerment is done by extending the tax object of several local taxes, introducingnew taxes, increasing the maximum tarif of several local taxes, and full discreation oftarif determination to local government. Control system was changed to a preventiveand corrective approach, by evaluating the draft of local regulations before they areadapted as local regulation, besides provocating local regulation that is against thehigher laws and regulations. Meanwhile, optimalization of tax collection and the useof local tax revenues is done by improving the share of provincial tax revenues toregions/cities, introducing of earmarking on several local taxes, and improving thearrangement of tax incentives. The local taxation reform was driven by the need forbetter implementation of local otonomy and fiscal decentralization policies, by grantingmore revenue sources to local government gradually. Devolution of a certain provincialtax and several central taxes to regions/cities can be seen as a reformulation ofnational tax system by redetermining the type of national taxes, provincial taxes, andregion/city taxes. Economic condition and tax potential varies among regions/cities inIndonesia. A special stragtegy is needed to assist and facilitate a certain region/cityin implementing the new local tax system. On the other hand, evaluation and improvementof local tax policies needs to be done continuously to develope an efficient and effectivelocal taxation system in Indonesia.